Sense-making Accountability: Netnographic Study of an Online Public Perspective. (2nd January 2017) - Aung, May; Bahramirad, Sina; Burga, Ruben; Hayhoe, Mychal-Ann; Huang, Shuyue; LeBlanc, Joshua
ABSTRACT: Accountability has been proposed and interpreted in multiple ways by scholars. However, the understanding of accountability from a public perspective, especially in the form of an enterprise offering public services, is not well understood. This study tries to shed light on accountability through a political crisis: the cancellation of power plants by the ruling political party in Ontario, Canada just prior to a provincial election. This study aims to extend our understanding of the multidimensional nature of accountability by gathering insights from the online public community. A netnographic approach was conducted on five social media sites. Six articles from these sites disseminating the crisis were selected and a total of 1313 associated comments were subjected to content analysis. We found the facets of accountability as perceived by the public somewhat differently from the perceptions of organisations. Multidimensional facets of sense-making accountability are identified, including the assigned meanings from the public (holders), the role of stakeholders (holders and holdees), the nature of public responses (emotional and reasoned responses) to a crisis and possible consequences (recommended actions) as suggested from the public. The recommended actions will ultimately help with the process of fostering accountability, and encouraging a new cycle of accountability development.